(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Human chorionic gonadotropin (HCG) is a glycoprotein hormone, which consists of two polypeptide subunits (alpha and beta), produced by syncytial trophoblast cells of the placenta during pregnancy. Ectopic HCG production occurs in many tumors including breast tumor. Objectives: The objective of the study is to investigate the expression of ?–HCG in breast tumor and its correlation with pathological prognostic factors (age, tumor type, site, size, histological grade, lymphocytic infiltration, vascular invasion and lymph node involvement). Methods: A total of 44 breast tumors were selected, consisting of eight benign lesions (Fibrocystic disease in four cases and fibroadenoma in the rest) and 36 malignant breast tumors (invasive ductal carcinoma (21 cases) all of not-otherwise-specified type (NOS), in situ ductal carcinoma (6 cases), invasive lobular carcinoma (6 cases) and in situ lobular carcinoma (3 cases). Results: ?-HCG expression was found in 6 of 36 malignant breast tumors (16.7%). None of the benign breast lesions showed ?-HCG expression. High expression of ?-HCG is seen more frequently in infiltrative ductal carcinoma with higher-grade tumor and in old age group (?50 years). Conclusion: It was concluded that high expression of b-HCG is seen more frequently in infiltrative ductal carcinoma with higher grade. There was a high b-HCG expression in tumors more than or equal to 5-cm diameter. Key words: Breast tumors, b-HCG